1979
DOI: 10.1002/ajh.2830060204
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced thrombocytopenia: Association with a platelet aggregating factor and arterial thromboses

Abstract: Eleven patients with heparin-induced thrombocytopenia were studied. Thrombocytopenia appeared 3-16 days following the initiation of prophylactic or therapeutic doses of heparin. The mean lowest platelet count recorded was 48,000/mm3. When heparin was stopped, recovery from thrombocytopenia began within 24 hours and was complete by ten days. Two patients developed fatal thromboses, and two others had myocardial infarctions while thrombo-cytopenic. In the serum of seven patients, including three of the four with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 18 publications
0
54
0
1
Order By: Relevance
“…110 In the second report, one out of 11 patients with suspected HIT received a platelet transfusion and had an inadequate increase in platelet count (but no thrombotic events). 111 More recently, a case series reported 37 patients with PF4-ELISA-confi rmed HIT who received one or more platelet transfusions during a 1-year period at a single center. 112 No thrombotic complications developed in any of the patients following platelet transfusion, and three deaths within a few days of transfusion were deemed unrelated to transfusion.…”
Section: Platelet Transfusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…110 In the second report, one out of 11 patients with suspected HIT received a platelet transfusion and had an inadequate increase in platelet count (but no thrombotic events). 111 More recently, a case series reported 37 patients with PF4-ELISA-confi rmed HIT who received one or more platelet transfusions during a 1-year period at a single center. 112 No thrombotic complications developed in any of the patients following platelet transfusion, and three deaths within a few days of transfusion were deemed unrelated to transfusion.…”
Section: Platelet Transfusionsmentioning
confidence: 99%
“…110,111 In the fi rst report, two out of fi ve patients with suspected HIT received a single platelet transfusion, one of whom developed arterial thromboembolism post transfusion (while still receiving heparin). 110 In the second report, one out of 11 patients with suspected HIT received a platelet transfusion and had an inadequate increase in platelet count (but no thrombotic events).…”
Section: Platelet Transfusionsmentioning
confidence: 99%
“…During the latter half of the 1970s, at least 7 groups of investigators [10][11][12][13][14][15][16] reported patients who resembled those of Rhodes and colleagues. Together, these studies provided further evidence of an Submitted February 14, 2008; accepted March 31, 2008.…”
Section: Platelet Activation In Hitmentioning
confidence: 99%
“…A common feature of these reports was evidence of platelet activation induced by patient serum, plasma, or purified immunoglobulin. [11][12][13][14][15][16][17] HIT: an immune disorder or a consumptive coagulopathy?…”
Section: Platelet Activation In Hitmentioning
confidence: 99%
See 1 more Smart Citation